Research themes and trends in the field of teacher educators: A topic modelling study - HANGÜL, TUĞBA (My University, 2024)
This study identified research themes in the field of teacher educators using topic modeling analysis and explored their trends over time. A dataset of 754 scientific publications from Scopus was analyzed with Latent Dirichlet Allocation approach. The findings revealed ten distinct research themes, covering pedagogy/knowledge, social justice, collaboration, identity, professional growth, policy, practice, quality standards, English language and technology competency. Thematic research trends exhibited periodic and consecutive patterns since the 2010s. The findings discussed the identified themes relative to existing review studies as well as trends considering the impact of education journals, educational policies and reforms initiatives, and Covid-19 pandemic.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Educational data science; Teacher educators; Text mining; Topic modeling; Research trends